UPAYA PENINGKATAN KINERJA GURU P3K MELALUI KEPEMIMPINAN DEMOKRATIS KEPALA SEKOLAH, KECERDASAN SPIRITUAL, DAN MOTIVASI KERJA GURU SEKOLAH DASAR NERGERI DI KECAMATAN GUNUNGSINDUR - Ridhayati Ridhayati; Sri Utaminingsih Utaminingsih; Ersam Mahendrawan Mahendrawan (STKIP Subang, 2026)
This study aims to analyze the influence of democratic leadership of school principals, spiritual intelligence, and work motivation on the performance of P3K teachers. The study employed a quantitative approach using a survey method. The population of this study consisted of P3K teachers, with the sample determined using an appropriate sampling technique. Data were collected through questionnaires, while data analysis was conducted using multiple linear regression with the assistance of statistical software. The results indicate that democratic leadership of school principals has a positive and significant effect on the performance of P3K teachers. Spiritual intelligence also has a positive and significant effect on teacher performance, indicating that spiritual values and meaningful work orientation play an important role in enhancing teacher performance. Meanwhile, work motivation has a significant effect on teacher performance with a negative direction, suggesting that work motivation dominated by external pressures may reduce the quality of teacher performance. Simultaneously, democratic leadership of school principals, spiritual intelligence, and work motivation have a significant effect on the performance of P3K teachers, with a coefficient of determination (R²) of 0.641. This indicates that 64.1% of the variance in P3K teachers’ performance can be explained by these three variables, while the remaining variance is influenced by other factors outside this study. The findings conclude that improving the performance of P3K teachers requires a comprehensive approach through strengthening democratic leadership, developing spiritual intelligence, and managing work motivation in a healthy manner oriented toward intrinsic motivation.